Pengaruh Disiplin Kerja dan Komunikasi terhadap Kinerja Karyawan pada PT Yeakin Plastic Industry di Kota Batam - Nofria Dewita (JURNAL PUNDI, 2020)
ABSTRACTThe purpose of this study was to determine the effect of work discipline and communication on the performance of employees of PT Yeakin Plastic Industry in Batam City. The population of PT Yeakin Plastic Industry amounted to 230, and sample 146. The research method used was associative causal. The research method uses a quantitative approach. The results of the study say valid and reliable, normal and there is no multicollinearity and heteroscedasticity. Partially, work discipline variables are stated to have a positive and significant influence on employee performance of 6,450 and partial communication variables have a positive and significant effect on employee performance at 6,036. Simultaneously, work and communication disciplines have a significant positive effect on employee performance at 154,882 and a significance level of 0,000. The conclusion of this study is that there are positive and significant influences on each independent variable on the dependent variables both partially and simultaneously. Keywords : Work Discipline, Communication, Performance